2015
DOI: 10.1038/mi.2014.58
|View full text |Cite
|
Sign up to set email alerts
|

Microbial sensing by goblet cells controls immune surveillance of luminal antigens in the colon

Abstract: The delivery of luminal substances across the intestinal epithelium to the immune system is a critical event in immune surveillance resulting in tolerance to dietary antigens and immunity to pathogens. How this process is regulated is largely unknown. Recently goblet cell associated passages (GAPs) were identified as a pathway delivering luminal antigens to underlying lamina propria (LP) dendritic cells (DCs) in the steady state. Here we demonstrate that goblet cells (GCs) form GAPs in response to acetycholine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
290
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(303 citation statements)
references
References 49 publications
12
290
1
Order By: Relevance
“…Alternatively, goblet cells induced by SPDEF may have a direct role in enhancing innate immune responses. Recent findings that goblet cells provide conduits for transepithelial delivery of tolerogenic antigens from the intestinal lumen to CD103 + DCs provide a precedent for a role for goblet cells in communicating with DCs to influence innate immune responses in epithelia (42).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, goblet cells induced by SPDEF may have a direct role in enhancing innate immune responses. Recent findings that goblet cells provide conduits for transepithelial delivery of tolerogenic antigens from the intestinal lumen to CD103 + DCs provide a precedent for a role for goblet cells in communicating with DCs to influence innate immune responses in epithelia (42).…”
Section: Discussionmentioning
confidence: 99%
“…S4A). By GSEA analysis, we compared our data with gene signatures of Goblet cells in both SI and colon (24), Paneth cells, enteroendocrine cells (8), and stem cells in SI (25). Reg4 + cells from colonic crypts resembled Paneth cells, and were less related to Goblet cells from colon or SI, or to enteroendocrine cells (Fig.…”
Section: Characterization Of Reg4mentioning
confidence: 99%
“…The unbiased gene set enrichment analysis was performed with Gene Set Enrichment Analysis (software.broadinstitute.org/gsea/index.jsp). Preranked lists of mean expression changes and input signatures were derived from published microarray and RNA-seq data (8,24).…”
Section: Microarray Analysis Single Lgr5-gfpmentioning
confidence: 99%
“…The potential of helminth-evoked changes in the enteric nervous system 95 and the regulation of mucus production by acetylcholine should also be pursued. 96 Finally, recent work has shown that goblet cells can sense their microenvironment and pass this information to dendritic cells; 97 the implications of this for barrier function and host-parasite interactions are poorly understood.…”
Section: Helminth and Host-derived Factors Impact On Intestinal Barrimentioning
confidence: 99%